Design, Development and Characterization of Losartan Pharmacosomes Encapsulated in Capsule Formulation - Gayathri, Kumararaja; Gandhi, Praveena; Kiruthika, S. (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: In comparison to conventional vesicular drug delivery techniques, Pharmacosomes are a potential method for vesicular drug delivery that offers a number of advantages. Pharmacosomes are phosphilipid complexes with the potential to increase the bioavailability of medicines that are poorly lipophilic and poorly water soluble. Angiotensin receptor blocker losartan is classified as a BCS class II medication with low solubility. Materials and Methods: Solvent evaporation method was used to prepare the Losartan Pharmacosomes. These prepared Pharmacosomes were encapsulated into capsules for easy administration. Results: The phospholipid complex of Pharmacosomes was made using the solvent evaporation method in 7 distinct ratios. The morphology, X-ray Diffraction, FTIR, UV and drug entrapment investigation of the synthesized losartan pharmacosomes were assessed. The synthesized compound was shown to have substantially better solubility than the pure medication Losartan. Losartan pharmacosomes were encapsulated into capsules for oral medication administration. Conclusion: Based on the results, we assume that the solubility as well as bioavailability problem of native losartan was reduced.
Keywords: Pharmacosomes; Losartan; Capsules; Solubility; Bioavailability